A novel efficient bioflocculant QZ-7 for the removal of heavy metals from industrial wastewater - Abu Tawila, Zayed M.M.; Ismail, Salmah; Abu Amr, Salem S.; Abou Elkhair, Emad K. (Royal Society of Chemistry, 2019)
In this study, a novel bioflocculant QZ-7 was produced from Bacillus salmalaya 139SI for industrial wastewater treatment. Biochemical analysis, FTIR, scanning electron microscopy-energy dispersive X-ray spectroscopy, and thermogravimetric analysis were performed. A synthetic wastewater sample was used to validate the performance of the prepared OZ-7 for the adsorption efficiency of As, Zn2+ Pb2+, Cu2+, and Cd2+ under optimal experimental conditions such as initial metal concentrations, pH, contact time (h) and QZ-7 adsorbent dosage (mg mL-1). The maximum removal efficiency for Zn2+ (81.3%), As (78.6%), Pb2+ (77.9%), Cu2+ (76.1%), and Cd2+ (68.7%) was achieved using an optimal bioflocculant dosage of 60 mg L-1 at 2 h shaking time, 100 rpm and pH 7. Furthermore, the obtained optimum experimental conditions were validated using real industrial wastewater and the removal efficiencies of 89.8%, 77.4% and 58.4% were obtained for As, Zn2+ and Cu2+, respectively. The results revealed that the prepared bioflocculant QZ-7 has the capability to be used for the removal of heavy metals from industrial wastewater. © 2019 The Royal Society of Chemistry.